Peningkatan Hasil Belajar Matematika Dengan Menerapkan Model Pembelajaran Team Games Tournament - Netty Nababan (JURNAL GLOBAL EDUKASI, 2018)
Abstract: Before class action, the level of mastery learning was 22.50% (out of 40 students only 9 people completed). In the first cycle after the action was carried out the student's completeness level became 80% (32 people completed from 40 students). In the second cycle after further action is taken as a result of reflection of the first cycle the percentage of students' completeness level becomes 95%. The activity of students in participating in mathematics learning after class action in the first cycle and second cycle increases. In the first cycle the average student attendance was 95.5% and in the second cycle it was 98.5%. Likewise in conducting learning activities there has been a fairly good change in behavior and students become independent. Keyword: team games tournament Abstrak: Sebelum dilakukan tindakan kelas, tingkat ketuntasan belajar adalah 22,50% (Dari 40 orang siswa hanya 9 orang yang tuntas). Pada siklus I setelah dilakukan tindakan tingkat ketuntasan siswa menjadi 80% (32 orang yang tuntas dari 40 siswa). Pada siklus ke 2 setelah dilaksanakan tindakan lebih lanjut sebagai hasil dari refleksi siklus I presentase tingkat ketuntasan siswa menjadi 95%. Keaktifan siswa dalam mengikuti pembelajaran matematika setelah dilakukan tindakan kelas pada siklus I dan siklus II semakin meningkat. Pada siklus I rata-rata kehadiran siswa 95,5% dan pada siklus II menjadi 98,5%. Demikian pula dalam melakukan aktivitas pembelajaran telah terjadi perubahan tingkah laku yang cukup baik dan siswa menjadi mandiri. Kata kunci: team games tournament